Characteristics of the Fractional Amplitude of Low-Frequency Fluctuation in Ocular Hypertension Patients: A Resting-State fMRI Study - Liang, Ying; Pan, Yi-Cong; Shu, Hui-Ye; Chou, Xue-Mei; Ge, Qian-Min; Zhang, Li-Juan; Li, Qiu-Yu; Liang, Rong-Bing; Li, Han-Lin; Shao, Yi (Frontiers in Medicine, 2022)
Background: The fractional amplitude of low-frequency fluctuation (fALFF) method has been underutilized in research on the pathogenesis and clinical manifestations of ocular hypertension (OH). Purpose: This study uses resting state functional magnetic resonance imaging (rs-fMRI) and fALFF to investigate the nature of spontaneous brain activity in OH patients and the relationship, if any, between changes in activity and clinical features. Materials and Methods: A total of 18 subjects (9 females and 9 males) with ocular hypertension (OH) and 18 healthy controls (HCs) matched for gender, age, and educational level were recruited to this study. All participants underwent an rs-fMRI scan, and spontaneous brain activity was assessed using the fALFF method. Receiver operating characteristic curves were plotted to investigate differences between OH and HC groups. Results: The fALFF values of OH patients were significantly higher in the left precuneus lobe (LP), compared with the same region in controls (P<0.05). Conversely, values in the left anterior cingulate lobe (LAC), were significantly lower (P<0.05) in OH than in controls. However, no significant association was found between the mean fALFF values and clinical characteristics in either brain area.